GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 19663 species occurrences available in GBIF matching the query: TaxonKey: Tachyglossidae. The dataset includes 19663 records from 78 constituent datasets: 18 records from Ghent University - Zoology Museum - Vertebrate collection. 3 records from SUI Vertebrate Collection. 15067 records from OEH Atlas of NSW Wildlife. 2 records from ISM Mammalogy Collection. 4 records from uconn-mammals. 19 records from MVZ Mammal Collection (Arctos). 94 records from Australian National Wildlife Collection provider for OZCAM. 2 records from Zoology (Museum of Evolution - Uppsala). 1 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 13 records from KUBI Mammalogy Collection. 4 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 8 records from CUMV Mammal Collection (Arctos). 900 records from Fauna Atlas N.T.. 27 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 255 records from Museum Victoria provider for OZCAM. 2 records from CRCM Vertebrate Collection. 2 records from Cowan Tetrapod Collection - Mammals. 1385 records from SA Fauna (BDBSA). 40 records from Field Museum of Natural History (Zoology) Mammal Collection. 3 records from MVZ Hildebrand Collection (Arctos). 3 records from Lund Museum of Zoology (MZLU). 2 records from Mammalogie ZMK. 39 records from Naturalis Biodiversity Center (NL) - Mammalia. 33 records from Museum of Comparative Zoology, Harvard University. 21 records from Tasmanian Museum and Art Gallery provider for OZCAM. 63 records from iNaturalist Research-grade Observations. 2 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 5 records from University of California Museum of Paleontology. 5 records from Mammals housed at MHNG, Geneva. 1 records from DMNS Mammal Collection (Arctos). 25 records from Mammal collection, Natural History Museum, University of Oslo. 7 records from naturgucker. 2 records from CAS Mammalogy (MAM). 4 records from UMMZ Mammal Collection. 4 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 42 records from Northern Territory Museum and Art Gallery provider for OZCAM. 2 records from LACM Vertebrate Collection. 2 records from Natural History Museum Rotterdam (NL) - Chordata collection. 2 records from Insecta ZMK. 132 records from Western Australian Museum provider for OZCAM. 50 records from Natural History Museum (London) Collection Specimens. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 1 records from Akita Prefectural Museum＋Mammalians Specimens of Akita Prefectural Museum. 47 records from NMNH Extant Specimen and Observation Records. 4 records from Collection Anatomie Histologie - SMF. 3 records from UWBM Mammalogy Collection. 4 records from UF Florida Museum of Natural History Mammals. 1 records from Mammal specimens. 1 records from LSUMZ Mammals Collection. 1 records from Paleobiology Database. 55 records from Individual Sightings. 2 records from Mammals Specimens. 1 records from (UTC) University of Tennessee Mammals Collection. 4 records from Mammal specimens. 17 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 3 records from University of Alberta Museum of Zoology Mammalogy Collection (UAMZ). 2 records from UCM Mammal Collection (Arctos). 2 records from PSM Vertebrates Collection. 2 records from Natural History Museum, University of Tartu. 2 records from UAZ Mammals. 13 records from Collection Mammalia SMF. 102 records from AMNH Mammal Collections. 165 records from Queensland Museum provider for OZCAM. 3 records from Auckland Museum Land Vertebrates Collection. 2 records from UAFMC Mammals. 1 records from Animal Sound Archive. 14 records from Bernice P. Bishop Museum. 1 records from Colección de Mastozoología. 26 records from Mammalogy Collection - Royal Ontario Museum. 50 records from Queen Victoria Museum Art Gallery provider for OZCAM. 486 records from Australian Museum provider for OZCAM. 2 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa).. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 3 records from NCSM Mammals Collection. 1 records from Auckland Museum Marine Collection. 6 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 5 records from Collection Mammalogie - ZSRO. 334 records from South Australian Museum Australia provider for OZCAM. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences